Forensic examination of Latin based handwriting samples according to writers' language levels as indicators of educational level. Issue 4 (29th October 2021) - Ozcan, Ekin; Emiral, Emrah; Canturk, Nergis; Canturk, Gurol
ABSTRACT: Forensic examinations and comparisons of handwriting are performed by analyzing several features, including allograph construction, alignment, pen pause, fluency, arrangement, punctuation, and pen pressure. In the present study, documents with the same content and written by 60 healthy volunteers in their native language, second language and, a language they did not know (as indicators of their educational level) were examined. These documents were compared in terms of forensic document examination parameters using a magnifier with an LED desk lamp and an optical glass lens. Statistically significant differences were identified in allograph construction, fluency, and punctuation ( p  = 0.001, p  = 0.000, and p  = 0.002, respectively). Handwriting was found to reflect a person's command of language and to provide clues regarding their education level, because the use of writing increases with education, and the level of language affects allograph construction, fluency, and punctuation. RésuméDes examens forensiques et des examens comparatifs d'écrits manuscrits sont effectués par l'analyse de plusieurs caractéristiques, telles que la construction allographique, l'alignement, les pauses du tracé, la fluidité, la disposition graphique, la ponctuation et la pression exercée par l'instrument d'écriture. Dans la présente étude, des documents possédant un contenu identique et rédigés par 60 volontaires en bonne santé, dans leur langue maternelle, dans une langue seconde ainsi que dans une langue qu'ils ne connaissaient pas (en tant qu'indicateurs de leur niveau d'éducation) ont été examinés. Ces documents ont été comparés en fonction de paramètres d'examen forensique de documents à l'aide d'une loupe composée d'une lampe de bureau à éclairage LED et d'une lentille en verre optique. Des différences statistiquement significatives ont été identifiées dans la construction des allographes, la fluidité et la ponctuation ( p  = 0, 001, p  = 0, 000 et p  = 0, 002, respectivement). L'écriture manuscrite s'est avérée bien refléter la maîtrise de la langue d'une personne et permet de fournir des indices à propos de son niveau d'éducation, puisque l'utilisation de l'écriture augmente avec le niveau d'éducation, et puisque le niveau de language exerce une influence sur la construction allographique, la fluidité et la punctuation.